Effect of diet on the fatty acids composition of cultured sea bass (Dicentrarchus labrax) liver tissues and histology compared with wild sea bass caught in Eagean Sea. - Aslı Müge Bilen; Soner Bilen (Marine Science and Technology Bulletin, 2013)
In the present study, the effect of diet on the fatty acids composition of cultured European sea bass liver tissues and histology when compared with wild sea bass caught in Eagean Sea was determined. In the study, the fish were fed with commercial feed for 90 days. In the liver tissue samples the amount of total lipid was higher in farmed than in wild fish. Henicosanoic fatty acid was found in commercial feed but not in fish liver. Fatty acid profiles in the livers reflected the fatty acid profiles of the commercial feeds. The dominant fatty acids in livers of cultured and wild sea bass were 16:0, 18:1n9, 18:2n6, C20:5n3 and 22:6n3. The results showed that cultured fish contained a higher level of EPA⁄DHA ratio and oleic acids, monounsaturated fatty acids, n-6 polyunsaturated fatty acids, whereas wild fish contained a higher level of saturated fatty acids, eicosapentaenoic acids, n-3 polyunsaturated fatty acids and n-3/n-6 ratio (P < 0.05). Commercial feed had effect on hepatic lipid droplets accumulation degree and pattern of vacuolization in the observed liver sections. The marked hepatic cell membrane degeneration and haemorrhagy on the liver observed in cultured sea bass was caused by the accumulation of very large lipid droplets. The hepatocyte nucleus size of fish was higher in farmed than in wild fish liver tissue (P < 0.05). Hepatocytes enlarged irregular nucleus located at the periphery of the cells. In conclusion, commercial feed had effect on farmed fish liver histomorphology. However, proper choice of dietary lipid would allow the fatty acid composition of cultured fish to be tailored to address the beneficial health aspects and consumer’s demands.